Pembangunan Sistem Informasi Pasien Operasi Dan Visite Untuk Tenaga Medis Berbasis Android Pada Rumah Sakit XYZ - Eki Yusandhi Iskandar; Herman Tolle; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In a public health institution, information flow is one of the most important things, especially to the medical personnel. Patient information, inpatient room information, and operation schedule are some of the most crucial information that a medical personnel has to acquire. Rumah Sakit XYZ is no exception, with a total of more than 200 medical personnel, the information flow to and from the medical person must be able to be accessed quickly and accurately. However there is not yet a platform for the medical personnel of Rumah Sakit XYZ to easily access basic information such as inpatient information, visitation, and operation. That is why, to help improve the business process in Rumah Sakit XYZ, and to give an insight as to the implementation of a solution for other health institution with a similar business process, an Android based information system for inpatient, visitation, and operation for medical personnel is built. The result of this system's implementation includes the fulfilment of all the functional requirement based on the requirement analysis, and the usability score of 79.5 based on the survey results to respondents usability testing using the SUS ( System Usability Scale) method, which means the system is in the Acceptable category.